Successful Treatment of Chronic Spontaneous Urticaria Associated with Autoimmune Thyroiditis: Clinical Case - Vera G. Kalugina; Leyla S. Namazova-Baranova; Elena A. Vishnyova; Anna A. Alexeyeva; Yliya Levina; Polina S. Arimova (Union of pediatricians of Russia, 2019)
Chronic spontaneous urticaria (CSU) can be associated with some autoimmune diseases which may affect the CSU course. Autoimmune thyroiditis can cause severe CSC. 2nd generation antihistamines are the golden standard of CSY therapy. However, even dose-escalation in some cases will not lead significant improvement. Nowadays there are not enough studies about other medications administration in children with CSU. Omalizumab is the only genetically engineered biologic drug for treatment of resistant (to standard therapy) forms of CSU, it can be used in children over 12 years old. We would like to present our data on one adolescent girl with CSU and comorbid autoimmune thyroiditis with thyroid function abnormality. The multidisciplinary approach to diagnostics and management of this patient as well as Omalizumab administration let us achieve total disease control and, finally, its remission.